2023
DOI: 10.1101/2023.06.15.545149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FLOWERING LOCUS Cdrives delayed flowering inArabidopsisgrown and selected at elevated CO2

Aleah Henderson-Carter,
Hannah Kinmonth-Schultz,
Lena Hileman
et al.

Abstract: Altered flowering time at elevated [CO2] is well documented, although mechanisms are not well understood. AnArabidopsisgenotype previously selected for high fitness at elevated [CO2] (SG) showed delayed flowering and larger size at flowering when grown at elevated (700 ppm) versus current (380 ppm) [CO2]. This response was correlated with prolonged expression ofFLOWERING LOCUS C(FLC), a vernalization-responsive floral repressor gene. To determine ifFLCdirectly delays flowering at elevated [CO2] in SG, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 55 publications
1
5
1
Order By: Relevance
“…Although the vernalization response pathway in addition to other floral integrator genes has been shown to be important for the [CO 2 ]-induced delay in SG [15,50], we did not note vernalization response genes to be altered here in SG. However, we noted that genes involved in the photoperiod and gibberellin-response pathways were altered.…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…Although the vernalization response pathway in addition to other floral integrator genes has been shown to be important for the [CO 2 ]-induced delay in SG [15,50], we did not note vernalization response genes to be altered here in SG. However, we noted that genes involved in the photoperiod and gibberellin-response pathways were altered.…”
Section: Discussioncontrasting
confidence: 58%
“…In fall-germinating, winter-annual variants of Arabidopsis, FLC stays high until it is repressed by prolonged cold (= vernalization) [49] likely so that FT rises and flowering occurs appropriately in warm, spring conditions. In subsequent work, we confirmed that downregulation of FLC through vernalization restored early flowering in SG in elevated [CO 2 ] [50]. However, the upstream mechanisms governing the response of FLC to [CO 2 ] are unknown.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations